2022
DOI: 10.3390/cancers14040954
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivation of MAPK Induces Tamoxifen Resistance in SPRED2-Deficient ERα-Positive Breast Cancer

Abstract: Breast cancer is the number one cause of cancer-related mortality in women worldwide. Most breast tumors depend on the expression of the estrogen receptor a (ERα) for their growth. For this reason, targeting ERα with antagonists such as tamoxifen is the therapy of choice for most patients. Although initially responsive to tamoxifen, about 40% of the patients will develop resistance and ultimately a recurrence of the disease. Thus, finding new biomarkers and therapeutic approaches to treatment-resistant tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 86 publications
(105 reference statements)
0
11
0
Order By: Relevance
“…1, B and C). We have recently shown that SPRED2 deficiency is an important indicator of tamoxifen resistance because of ERα hyperactivation through the MAPK signaling pathway ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…1, B and C). We have recently shown that SPRED2 deficiency is an important indicator of tamoxifen resistance because of ERα hyperactivation through the MAPK signaling pathway ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…The approach is based on a phenotypic assay of the cellular ATP levels, which reflect the metabolic activity, and hence, the viability of cells. We initially screened drug combinations using the three ERα+ breast cancer cell lines, MCF7 (tamoxifen-sensitive), MCF7-V (a more tamoxifen-tolerant variant of MCF7) (Vafeiadou et al , 2022; Mohammadi Ghahhari et al , 2022), and MCF7/LCC2 (tamoxifen-resistant) (Brünner et al , 1993). In parallel, we used MCF10A, a non-malignant breast epithelial cell line, to monitor the relative toxicity, and to calculate the therapeutic window (TW), which represents the difference in efficacy between cancerous and non-cancerous cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, ERα can be activated in an estrogen- independent manner by a large panel of factors, including epidermal growth factor (EGF) (Ignar-Trowbridge et al , 1992; Ignar-Trowbridge et al , 1993), insulin and insulin-like growth factors (IGF) (Newton et al , 1994), PI3K (Campbell et al , 2001), Akt (Campbell et al , 2001; Martin et al , 2000), and hypoxia-inducible factor 1 α (HIF1α) (Cho et al , 2006; Bennesch & Picard, 2015) (see detailed list at https://www.picard.ch/downloads/Factors.pdf). Through various domains, ERα can interact with a plethora of proteins that regulate its activity, such as the MAPKs ERK1/ERK2 (ERK1/2) (Chen et al , 2002; Kato et al , 1995; Kim et al , 2021; Vafeiadou et al , 2022; Li et al , 2012; Mueller et al , 2000; Bunone et al , 1996), mTOR (Alayev et al , 2016), cyclin-dependent kinase inhibitor 1 (p21) (Fritah et al , 2005; Redeuilh et al , 2002; Abukhdeir et al , 2008), and poly (ADP-ribose) polymerase 1 (PARP1) (Schiewer & Knudsen, 2014; Zhang et al , 2013; Pulliam et al , 2019; Gadad et al , 2021) (see the updated list of ERα interactors at https://www.picard.ch/downloads).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NF1-knockout MCF7 cells showed increased levels of phospho-ERK and resistance to fulvestrant, which could be reverted by ERK inhibitors [ 85 ]. Similarly, downregulation of Sprouty-related EVH1 domain containing 2 (SPRED2), a member of the Sprouty family of RAS inhibitors, frequently altered in breast cancer due to deletion or promoter methylation, leads to tamoxifen resistance, which can be overcome in breast cancer cell lines by a combination of the ERK 1/2 inhibitor ulixertinib with tamoxifen [ 112 ]. RAS mutations have been identified in circulating tumor DNA in 15% of patients who had disease progression under aromatase inhibitors, potentially mediating resistance [ 113 ].…”
Section: Ras/raf/mek/erk Pathway In Luminal Cancers and Resistance To...mentioning
confidence: 99%